Innovative Sunday School Strategy Shaping the Character of Generation Alpha - Jemmy, Jemmy; Effendi, Daniel Tatang (World Psychology, 2024)
This research explores innovative strategies to shape the character of Generation Alpha within Sunday School settings, addressing the challenges posed by technological advancements and generational shifts. Employing a qualitative approach and thematic analysis, the study reviews literature on Sunday School innovations, technology integration, character formation, and project-based learning. It identifies key themes: the historical origins of Sunday Schools, the integration of technology in Sunday School learning, character education through storytelling, and project-based learning. Findings underscore the significance of Sunday Schools in shaping moral character and adapting to contemporary needs. Examples of effective technology-based learning media are discussed, emphasizing the importance of aligning content with Christian values. Project-based learning is highlighted as a means to internalize Christian values and promote empathy and responsibility. Blended learning approaches are suggested to enhance motivation and engagement. This research contributes insights and recommendations for educators and church leaders to effectively mold the character of Generation Alpha within Sunday School contexts.